Ensino de Semicondutores no Ensino Médio usando Softwares Educacionais e Design Thinking - Santos, Giullyano Cordeiro dos (2025)
Teaching semiconductor content in high school can be a considerable challenge. This work aims to develop an effective methodology for teaching semiconductors in high school by integrating theory and practice. The sociocultural theory of Vygotsky, combined with Design Thinking and digital tools such as Tinkercad and Falstad platforms, was employed. The intention is to make physical concepts more accessible and engaging for students, promoting social interaction, collaboration, and learning, thus preparing them for scientific careers in an increasingly technological society. Data collected during implementation demonstrated that this strategy was effective, promoting greater conceptual understanding and student engagement. The integration of virtual simulation, Design Thinking, and collaborative learning facilitated teaching abstract concepts, making Physics more dynamic and relatable for students. Results indicate that combining technology, active methodologies, and contextualized teaching not only expands scientific comprehension but also prepares students for a world increasingly reliant on science and technology. Thus, connecting Physics to everyday life through digital tools makes learning more meaningful and lasting.